Estado de los recursos pesqueros en la zona norte del Pacífico colombiano ante la implementación de la Zona Exclusiva de Pesca Artesanal – ZEPA, en un contexto socioecosistémico (2020)
Globally there is a crisis due to the accelerated detriment of fishery resources, largely due to weak governance, lack of management and lack of knowledge. In Colombia, some management tools have been implemented to move towards co-management of fishery resources, highlighting the Exclusive Artisanal Fishing Zone (ZEPA) of the Colombian Pacific. The present research contributes to the knowledge of the state of the fishing resources and to the analysis of the management of the north zone of the Colombian Pacific, after the implementation of the ZEPA. It collects the fishery data of the area, registered by governmental institutions and NGOs, to analyze the interannual dynamics and compare the effects of the implementation of the ZEPA, in particular with indices such as landing by unit of effort, maximum sustainable yield and effort. Likewise, qualitative information was obtained, through four focus groups, with the participation of 27 fishers and 15 semi-structured interviews with researchers, in order to assess the state of the eight principles proposed by economist Elinor Ostrom for a successful co-management of the resources in the ZEPA. In addition, a catch quota from the MSY is proposed for each of the fishing gear and species of commercial importance, following the precautionary approach proposed by FAO. With the results, a vision of the state of the Ostrom principles was built, evidencing the willingness of fishermen to move towards collective management of resources, as well as the urgency of strengthening the monitoring of resources and rules and agreeing sanctions for Violators. This study highlights the strengths of the ZEPA in Colombia and presents the minimum factors required to strengthen and managed it effectively in the immediate future.